The witch's warning - Mann, Greyson (Mann, Greyson. Secrets of an overworld survivor, 2017)
After lightning hits Will's village and turns one of his friends into a witch, Mina and Will head to the witch huts in the swamp to save their friend but instead encounter dangerous witches that are capable of out-battling Mina.